Orang Asing Yang Berada Di Indonesia Berdasarkan Ketentuan Undang – Undang Nomor 6 Tahun 2011 Tentang Keimigrasian - Tita Jolanda Anggraini Sahetapy; Johanis Steny Franco Peilouw; Irma Halima Hanafi (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
Immigration is a matter of regulating the traffic of people entering or leaving the Territory of the Republic of Indonesia and its supervision in the context of maintaining state sovereignty. Purpose of the Research: Based on this, the problem in this writing is